Disaster curriculum development at TK Negeri Cempaka Jaya Kota Pekalongan - Sri Elly Yunara (Himpunan Pengembang Kurikulum Indonesia, 2026)
Disaster education is an urgent need given the high potential threat of flooding in Pekalongan City, Central Java Province. Disaster education in Early Childhood Education (Pendidikan Anak Usia Dini or PAUD) remains teacher-centered and does not yet employ a systematic, structured curriculum. This study aims to develop and implement a project-based disaster curriculum at Cempaka Jaya State Kindergarten in Pekalongan City to improve early childhood disaster preparedness. Cempaka Jaya State Kindergarten is located in an area with a high risk of flooding, including tidal flooding. The research on the development of a project-based disaster curriculum in Cempaka Jaya State Kindergarten uses a qualitative approach, drawing on research and development, and refers to the ADDIE (analysis, design, development, implementation, and evaluation) model. The development of a project-based disaster curriculum in PAUD is effective in instilling knowledge, skills, and attitudes of disaster preparedness through contextual, collaborative learning, critical thinking, and disaster problem-solving in the surrounding environment. The effectiveness of disaster learning can also be increased, especially for those centered on students, in accordance with local geographic conditions and the developmental stages of early childhood. Abstrak Pendidikan kebencanaan menjadi kebutuhan mendesak mengingat potensi ancaman banjir yang tinggi di Kota Pekalongan, Provinsi Jawa Tengah. Pendidikan kebencanaan di PAUD masih berpusat pada guru dan belum menggunakan kurikulum yang sistematis dan terstruktur. Penelitian ini bertujuan untuk mengembangkan dan mengimplementasikan kurikulum kebencanaan berbasis proyek di TK Negeri Cempaka Jaya, Kota Pekalongan, guna meningkatkan kesiapsiagaan anak usia dini dalam menghadapi bencana. TK Negeri Cempaka Jaya terletak di daerah yang memiliki potensi risiko bencana banjir dan rob tinggi. Penelitian pengembangan kurikulum kebencanaan berbasis proyek di TK Negeri Cempaka Jaya menggunakan pendekatan kualitatif dengan jenis penelitian research and development dan mengacu pada model ADDIE (analysis, design, development, implementation, evaluation). Pengembangan kurikulum kebencanaan berbasis proyek di PAUD efektif untuk menanamkan pengetahuan, keterampilan, dan sikap kesiapsiagaan terhadap bencana melalui pembelajaran kontekstual, kolaboratif, berpikir kritis, serta pemecahan masalah kebencanaan di lingkungan sekitar. Efektivitas pembelajaran kebencanaan juga dapat meningkat, terutama yang berpusat pada murid, sesuai dengan kondisi geografis lokal serta tahap perkembangan anak usia dini. Kata Kunci: kesiapsiagaan bencana; pembelajaran berbasis proyek; pendidikan anak usia dini; pendidikan kebencanaan